Animal traction and small - scale mechanization - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Draught animal power is making a greater contribution than ever before to global food production. Economically efficient andeasy to use, animal traction not only reduces fuel-oil costs but also provides the added benefit of manure. Farmers'...